Mapping the research landscape of immune response in human brucellosis: a bibliometric analysis - Wang, Lingling; Lu, Peipei; Wang, Xuhong; Song, Xue; Tong, Xuewei; Yang, Shuting; Li, Zhiwei (Frontiers in Microbiology, 2025)
IntroductionBrucella bacteria are adept at evading the human immune system, leading to a chronic infectious disease known as brucellosis, which poses significant global health challenges. This study addresses a notable gap in bibliometric analyses concerning the immune response to brucellosis.MethodsWe conducted a comprehensive literature screening from the Web of Science Core Collection, covering publications from 1980 to 2024. Relevant publications were analyzed using R software, VOSviewer, and CiteSpace for bibliometric analysis.ResultsA total of 733 publications were included in this study, revealing an average annual growth rate of 5.91% in publications. The United States led in publication volume and citations, followed by China and France. Prominent research institutions included INSERM (France) and CONICET (Argentina). Infection and Immunity was identified as a leading journal in the field, publishing 97 papers with 5,184 citations. Keyword co-occurrence analysis delineated three main research clusters: Brucella vaccine development and immune protection, Brucella molecular mechanisms and intracellular survival strategies, and host innate immunity and Brucella interaction mechanisms. Burst analysis highlighted increasing attention on keywords such as “protection,” “type IV secretion system,” “pathogenesis,” and “prediction” since 2018.DiscussionThis bibliometric analysis sheds light on the global research landscape regarding the immune response in human brucellosis, pinpointing trends and gaps, with a focus on immune escape mechanisms and the future development of safe, effective vaccines.